Analyzing stakeholder perceptions of the Public Health Emergency Credit Act and decarceration during the COVID-19 pandemic - Azari, Anthony M. (Journal of crime and justice, 2025)
Drawing from semi-structured interviews, this paper examines the perspectives of 14 criminal justice stakeholders who were integral in creating and implementing the New Jersey Public Health Emergency Credits Act (2020). Stakeholders, including police administrators, corrections administrators, parole administrators, prison health administrators, and reentry service organization administrators, were interviewed. Stakeholders shared their viewpoints through three phases of the bill (pre-implementation, implementation, and post-implementation), highlighting their struggles with the lack of time and resources to support individuals upon their release, which later impacted their supervision capabilities. Implications suggest that future decarceration efforts may benefit from augmented planning and coordination.